Pengaruh Metode Inkuiri Dengan Bantuan Audio Visual Terhadap Hasil Belajar Agama Islam di SMP Swasta YP Utama - Harahap, Kurnia Febriani (Universitas Labuhanbatu, 2023)
Education is the main factor in efforts to advance the nation. Overall, education is part of a country's progress. The inquiry method can be classified as a relatively new method that has been offered by education experts. This inquiry method is considered relevant today, because its function can really ignite students' creativity in thinking and reasoning activities. Â This type of research is quantitative research. The location of this research was carried out at YP UTAMA PRIVATE SMP SCHOOL on Jalan Suluh No. 80A, Sidorejo Hilir, Kec. Medan Tembung, Medan City. When this research was carried out in March 2023. This inquiry method research with audio visual assistance had an influence on student learning outcomes at SMP YP UTAMA with the average posttest score (after using the method) being 77 while the average pretest score (before using method) has an average value of 58. The hypothesis results using Test-Test show that the sample results show that the T-2tailed significance value is <0.001 <0.05, so it is in accordance with the basis for decision making. Ho is rejected. Meanwhile, the tcount value is -4.627 < ttable is 2.021, then Ho is accepted.